9-5=4 Therefore f=4
Hope this helps
Answer:
Step-by-step explanation:
<u>Given function</u>
<u>To find</u>
<u>Solution</u>
Substitute x with 3 in the equation to find f(3)
- f(3) = -4(3+3) = -4*6 = -24
A = Anthony's weight
B = Anthony's brother's weight
A = 2B + 9 Plug in Anthony's weight
59 = 2B + 9 Subtract 9 from both sides
50 = 2B DIvide both sides by B
25 = B Switch the sides to make it easier to read
B = 25
Anthony's brother weighs 25 pounds.
(f * g)(x) = 4x^2(x + 1)
4x^3 + 4x^2
Answer:
3, 15, 14
Step-by-step explanation:
x + 5x + ( 5x -1) = 32
11x - 1 = 32
11x = 32 + 1
11x = 33
11x/11 = 33/11
x = 3
therefore
the first number is 3
the second is 5 × 3 = 15
the third number is 15 - 1 = 14